2010
DOI: 10.1007/978-3-642-17316-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Best Clustering Configuration Metrics: Towards Multiagent Based Clustering

Abstract: Abstract. Multi-Agent Clustering (MAC) requires a mechanism for identifying the most appropriate cluster configuration. This paper reports on experiments conducted with respect to a number of validation metrics to identify the most effective metric with respect to this context. This paper also describes a process whereby such metrics can be used to determine the optimum parameters typically required by clustering algorithms, and a process for incorporating this into a MAC framework to generate best cluster con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Note that the chosen value of t can significantly affect the number of Clustering Agents that are spawned. The authors proposed a method, in the context of MABC, to identify the most appropriate value for t in [10] where they reported on experiments conducted with respect to a number of cluster validation techniques to identify the optimum parameters for clustering algorithms. In [10] the desired final configuration was generated using a sequence of parameter values to produce a collection of cluster configurations from which the most appropriate was selected.…”
Section: Biding Phase Founded On the K-nn Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the chosen value of t can significantly affect the number of Clustering Agents that are spawned. The authors proposed a method, in the context of MABC, to identify the most appropriate value for t in [10] where they reported on experiments conducted with respect to a number of cluster validation techniques to identify the optimum parameters for clustering algorithms. In [10] the desired final configuration was generated using a sequence of parameter values to produce a collection of cluster configurations from which the most appropriate was selected.…”
Section: Biding Phase Founded On the K-nn Paradigmmentioning
confidence: 99%
“…The authors proposed a method, in the context of MABC, to identify the most appropriate value for t in [10] where they reported on experiments conducted with respect to a number of cluster validation techniques to identify the optimum parameters for clustering algorithms. In [10] the desired final configuration was generated using a sequence of parameter values to produce a collection of cluster configurations from which the most appropriate was selected. These reported experiments clearly demonstrated that there was no single "best" value for t. From the experiments it was also clear there were many factors that influence the choice of the best value for t, such as the nature of the data set size, distribution of values, number of potential clusters and so on; consequently it was not possible to identify specific correlations between t values and the nature of the data set.…”
Section: Biding Phase Founded On the K-nn Paradigmmentioning
confidence: 99%
“…Sum of squared error (SSE) is calculated by summing the squared distance between the cluster centroid (Cen i ) and every object within the cluster [7]. To determine the best cluster configuration we try to minimize SSE.…”
Section: Sum Of Squared Error(sse)mentioning
confidence: 99%
“…Note that the chosen value of t can significantly affect the number of Clustering Agents that are spawned. The authors proposed a method to identify the most appropriate value for t in [5].…”
Section: Biding Phase Founded On the Knn Spawning Strategymentioning
confidence: 99%